Collective sport team collapse - a process model - Wergin, V. V. (Technische Universität München, 2019)
Collective sport team collapse can be described as a sudden, collective, and dramatic drop in performance of a sports team within a game. Although most team sport athletes are familiar with the phenomenon and agree that it plays an important role for the outcome of games or competitions, research in the area of collective sport team collapse is still in its infancy. This dissertation project reveals causes of collective team collapse, defines the phenomenon, and distinguishes it from other dynamic team processes. It furthermore tests selected causes of collective team collapse in the field and provides practical implications for athletes and coaching staff members. The dissertation involves two qualitative studies investigating causes of collective team collapse through the perceptions of athletes, coaches, and sport psychologists. A third quantitative study explores the phenomenon of collective team collapse in the field and further quantifies the role of negative emotion as a cause of collective sport team collapse. The first two studies reveal that collective sport team collapse is evoked by a cascade of triggers rather than by single causes. This cascade includes antecedents which make the occurrence of a team collapse more likely, critical events on the court which trigger the actual team collapse, and cognitive, affective, and behavioral outcomes that maintain the collapse and prohibit the team`s recovery. Results further show that certain factors seem to play a special role in team collapse situations. In this regard, all participant groups described social processes, as for example the transfer of negative emotions or decreased performance, to be important factors influencing the course of a team collapse. The third study shows that collective sport team collapse manifests itself in a reduced running performance of players compared to lost game situations without the experience of collective collapse. Further results reveal that especially negative emotions are involved in the process of collective team collapse, where they are higher compared to lost game situations. While the first two studies give an insight into the process of factors causing a team collapse, study three is the first study to quantify collective team collapse situations in the field. It furthermore quantifies the association between negative emotions and the occurrence of team collapse although the causal relation between negative emotion and team collapse needs to be investigated in depth in future research. In a final evaluation, team collapse is analyzed in the light of existing theories in the field of work and organizational psychology and relations between collective team collapse and other team phenomena are discussed. Building up on this, possible directions for future research are provided.